Total Numbers and Movements of Photo‐Identified Subantarctic (Type D) Killer Whales - Jared R. Towers; Paul Tixier; Christophe Guinet; Nicolas Gasco; John P. Y. Arnould; Ted Cheeseman; Robert L. Pitman (Marine Mammal Science, 2026)
The distinctive Subantarctic (Type D) killer whale (DKW) ( Orcinus orca ) is a highly divergent and apparently inbred form previously known only from three mass strandings and several dozen at‐sea sightings, primarily from Patagonian toothfish ( Dissostichus eleginoides ) longline vessels in the southern Indian Ocean and from tourism vessels in the Scotia Sea. Its range appears to be circumpolar throughout the Subantarctic, but very little is known about total numbers and overall movements. We summarize photo‐identification data from 352 of 406 sightings collected between 44° S and 62° S from 2003 to 2024. Among 207 photo‐identified individuals there were two distinct clusters of 78 and 29 toothfish depredators, one in the southern Indian Ocean and the other off southern Chile, respectively. An additional 100 DKW were photo‐identified throughout the wider Subantarctic. Discovery curves indicate that DKW may be more abundant than some less divergent or inbred killer whale populations. Depredating DKW showed seasonal and interannual site fidelity, but 10 depredating individuals identified in the southern Indian Ocean were also resighted in the southern South Atlantic, 4428 km away. Probable re‐sightings of two other DKW occurred in the Scotia Sea over distances of 1070 and 41 km, respectively. These latitudinally narrow, long‐distance inter‐ocean movements are unique among killer whales. During the study period, the entirely pelagic distribution of encounters appears to have shifted significantly southward.

Tracking data reveal both indirect and direct interactions between killer whales and fisheries in subantarctic waters - Vinicius Robert; Anaïs Laurioux; Ryan R. Reisinger; Jared R. Towers; Erwan Auguin; Margaux Mollier; Gaëtan Richard; P.J. Nico de Bruyn; Christophe Guinet; Paul Tixier (Marine Environmental Research, 2026)

The Foraging Success of Southern Elephant Seals ( Mirounga leonina ) Dispersing to the West and East of the Kerguelen Archipelago - Connor McGarry; David B. Green; Clive R. McMahon; Christophe Guinet; Rob Harcourt; Baptiste Picard; Sophie Bestley (Marine Mammal Science, 2026)
Foraging behavior and success are a function of prey abundance and distribution in marine environments. Oceanographic processes shape prey spatial structuring, leading to some areas of high heterogeneity and others of high homogeneity, causing marine predators to exhibit different at‐sea behaviors. Our study investigated foraging success and effort of adult female southern elephant seals dispersing west or east of the Kerguelen Plateau. We quantified drift dive data and dive metric data for 153 seals, focusing on timing and spatial patterns in seal buoyancy change and its relationship with seal dive behavior. We assessed whether differences were linked to differing responses to forage quality. Overall, buoyancy changes indicated elephant seals had similar foraging success in both homogeneous (west) and heterogeneous (east) environments around the Kerguelen Plateau. Seals to the east dived deeper, with shorter hunting times and higher descent rates, probably related to higher mesoscale activity, while those to the west had lower descent rates and focused on shallower prey. Both groups responded to changes in forage quality by increasing ascent/descent rate in high‐quality areas. These results suggest that these seals behave as predicted by the marginal value theorem and in so doing adapt foraging behavior to efficiently exploit profitable prey patches.

Elephant seals as sentinels of the ongoing changes affecting the Southern Ocean: Disentangling environmental and maternal effects on pup size and body condition - Nicolas Séon; Vinicius Robert; Clive R. McMahon; Robert G. Harcourt; Mark Hindell; Alexandra Scheubel; Gaël Guillou; Paco Bustamante; Baptiste Picard; Christophe Guinet (Science of The Total Environment, 2025)

Divergent killer whale populations exhibit similar acquisition but different healing rates of conspecific scars - Celine van Weelden; Paul Tixier; Thomas Doniol-Valcroze; Christophe Guinet; Jared R. Towers (Behavioral Ecology and Sociobiology, 2025)
Scars obtained from interactions with conspecifics may be caused by both playful and aggressive activities, making them useful when studying cetacean behaviour. This study investigates the effects of age and sex on conspecific scar acquisition and healing in three genetically distinct populations of killer whales ( Orcinus orca ) each with unique diets and social structures. The sample consisted of 50 of the most commonly photo-identified individuals from all sex and age classes in each of the Bigg’s, Northern Resident, and Crozet killer whale populations. The number of new scars annually acquired by an individual as well as how long it took them to disappear were extracted from annual photo-identification images of these individuals taken between the years of 2008 and 2021. Scar acquisition was analysed using a generalized additive model while scar healing was assessed using Kaplan-Meier survival curves. Results showed an inverse relationship between scar acquisition and age, as well as an effect of sex with males being more scarred than females amongst all age classes. No significant differences in scar acquisition between populations was found. Scar re-pigmentation was faster in Northern Residents compared to Crozet and Bigg’s individuals and varied amongst age classes, with scars on calves and juveniles disappearing more quickly than those on adults. These population- and age-based differences in healing may be due to scar severity, while results around scar acquisition suggest that the nature of physical interactions between sex and age classes in this species are homogenous despite cultural and genetic differences that have evolved between populations.

Adding a diversity of legumes to a crop decision-support system: Maintaining satisfactory accuracy while keeping the model simple - M. Bedu; L. Lefèvre; A. Dupont; P. Dubrulle; R. Reau; P. Debaeke; M. Guinet; M.-H. Jeuffroy; P. Maury; A. Schneider; C. Schoving; P. Thiébeau; et al. (European Journal of Agronomy, 2023)

First description of in situ chlorophyll fluorescence signal within East Antarctic coastal polynyas during fall and winter - Lucie Bourreau; Etienne Pauthenet; Loïc Le Ster; Baptiste Picard; Esther Portela; Jean-Baptiste Sallée; Clive R. McMahon; Robert Harcourt; Mark Hindell; Christophe Guinet; Sophie Bestley; Jean-Benoît Charrassin; et al. (Frontiers in Marine Science, 2023)
Antarctic coastal polynyas are persistent and recurrent regions of open water located between the coast and the drifting pack-ice. In spring, they are the first polar areas to be exposed to light, leading to the development of phytoplankton blooms, making polynyas potential ecological hotspots in sea-ice regions. Knowledge on polynya oceanography and ecology during winter is limited due to their inaccessibility. This study describes i) the first in situ chlorophyll fluorescence signal (a proxy for chlorophyll-a concentration and thus presence of phytoplankton) in polynyas between the end of summer and winter, ii) assesses whether the signal persists through time and iii) identifies its main oceanographic drivers. The dataset comprises 698 profiles of fluorescence, temperature and salinity recorded by southern elephant seals in 2011, 2019-2021 in the Cape-Darnley (CDP;67˚S-69˚E) and Shackleton (SP;66˚S-95˚E) polynyas between February and September. A significant fluorescence signal was observed until April in both polynyas. An additional signal occurring at 130m depth in August within CDP may result from in situ growth of phytoplankton due to potential adaptation to low irradiance or remnant chlorophyll-a that was advected into the polynya. The decrease and deepening of the fluorescence signal from February to August was accompanied by the deepening of the mixed layer depth and a cooling and salinification of the water column in both polynyas. Using Principal Component Analysis as an exploratory tool, we highlighted previously unsuspected drivers of the fluorescence signal within polynyas. CDP shows clear differences in biological and environmental conditions depending on topographic features with higher fluorescence in warmer and saltier waters on the shelf compared with the continental slope. In SP, near the ice-shelf, a significant fluorescence signal in April below the mixed layer (around 130m depth), was associated with fresher and warmer waters. We hypothesize that this signal could result from potential ice-shelf melting from warm water intrusions onto the shelf leading to iron supply necessary to fuel phytoplankton growth. This study supports that Antarctic coastal polynyas may have a key role for polar ecosystems as biologically active areas throughout the season within the sea-ice region despite inter and intra-polynya differences in environmental conditions.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Inferring Variation in Southern Elephant Seal At-Sea Mortality by Modelling Tag Failure - Angus F. Henderson; Clive R. McMahon; Rob Harcourt; Christophe Guinet; Baptiste Picard; Simon Wotherspoon; Mark A. Hindell (Frontiers in Marine Science, 2020)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Observations of a distinctive morphotype of killer whale (Orcinus orca), type D, from subantarctic waters - Robert L. Pitman; John W. Durban; Michael Greenfelder; Christophe Guinet; Morton Jorgensen; Paula A. Olson; Jordi Plana; Paul Tixier; Jared R. Towers (Polar Biology, 2011)

Survival rate, abundance, and residency of long‐finned pilot whales in the Strait of Gibraltar - P. Verborgh; R. De Stephanis; S. Pérez; Y. Jaget; C. Barbraud; C. Guinet (Marine Mammal Science, 2009)
Long‐finned pilot whales in the Strait of Gibraltar are distributed over the main shipping routes. This exposes them to risks of collisions and probable acoustic and physical disturbance. This species is also the target of whale‐watching operations. The aim of this study was to estimate the annual population size, survival rate, and population growth rate of pilot whales occurring in the Strait and their inter‐annual variation using photo‐identification. A robust design was used to estimate all three parameters. A total of 10,784 individual pilot whale fins were photographed and analyzed. The population size estimation in summer ranged from a low of 147 individuals in 1999 to a high of 265 individuals in 2003. The annual population growth rate was estimated from mark recapture models to be 5.5%. The survival rate of adults was estimated at 0.982 (95% CI: 0.955–0.993). The same individuals have been observed between years. This suggests that this population is resident in the Strait, at least during summer. This study provides baseline knowledge prior to a predicted increase in shipping traffic throughout the main foraging area due to the opening in 2007 of a major shipping harbor along the Moroccan coast of the Strait.

WISE-2005: effect of aerobic and resistive exercises on orthostatic tolerance during 60 days bed rest in women - Patrick Guinet; Suzanne M. Schneider; Brandon R. Macias; Donald E. Watenpaugh; Richard L. Hughson; Anne Pavy Le Traon; Jean-Yves Bansard; Alan R. Hargens (European Journal of Applied Physiology, 2009)

Long-term social structure of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; P. Verborgh; S. Pérez; R. Esteban; L. Minvielle-Sebastia; C. Guinet (acta ethologica, 2008)

Diet of the social groups of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; S. García-Tíscar; P. Verborgh; R. Esteban-Pavo; S. Pérez; L. Minvielle-Sebastia; C. Guinet (Marine Biology, 2008)

Evaluation of Six Commercial Systems for Identification of Medically Important Yeasts - L. Buchaille; A. M. Freydière; R. Guinet; Y. Gille (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Evaluation of six commercial systems for identification of medically important yeasts - L. Buchaille; A. M. Freydière; R. Guinet; Y. Gille (European Journal of Clinical Microbiology & Infectious Diseases, 1998)